PENGARUH KARAKTERISTIK PEROKOK AKTIF PADA PENDERITA HIPERTENSI DI UPT PUSKESMAS DASUK - Mujib Hannan; Zakiyah Yasin; Syaifurrahman Hidayat (Wiraraja Medika : Jurnal Kesehatan, 2017)
Smoking is one of the habits that can affect blood pressure, from the data UPT PuskesmasDasuk number of people with hypertension in 2011 patients reported as much as 7.85% and8.05% in 2012 as many people with it have increased. This study was conducted to determinePreview Smoker Active In Patients with Hypertension In UPT Puskesmas Dasuk Sumenep CityDistrict in 2016..Descriptive research design. Population of hypertensive patients in UPT Puskesmas Dasuk in2016 as many as 146 people. Sample were 29 respondents to the inclusion criteria were activesmokers with hypertension and at UPT clinic Dasuk. Variabelnya is characteristic of activesmokers. Collecting data using questionnaires, the data were, conclusions and suggestions.Nearly half of the 29 respondents 14 (48.3%) aged 60-74 years, the majority of 17 (58.6%)had elementary / Not The End SD, 9 Nearly half (31.0%) work Entrepreneurs, Nearly Half 13(44.9%) respondents blood pressure stage 3, Most of the 20 (69.0%) smoked more than> 10 in aday, Most of the 17 (58.6%) smoked> 20 years., Most of the 19 (65.5 %) smoked type of filter.,Most of the 16 (55.1%) smoked after a meal.Nurse attempts to overcome the problem of active smokers in patients with hypertension inUPT Puskesmas Dasuk to provide information about the dangers of cigarette smoking is expectedto know about the dangers of smoking and nothing else.